2014
DOI: 10.1515/em-2012-0010
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Analysis with Multiple Mediators

Abstract: Recent advances in the causal inference literature on mediation have extended traditional approaches to direct and indirect effects to settings that allow for interactions and non-linearities. In this paper, these approaches from causal inference are further extended to settings in which multiple mediators may be of interest. Two analytic approaches, one based on regression and one based on weighting are proposed to estimate the effect mediated through multiple mediators and the effects through other pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
744
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 657 publications
(749 citation statements)
references
References 21 publications
5
744
0
Order By: Relevance
“…Specifically, if the aforementioned ignorability conditions A1-A4 hold with respect to each mediator separately 11 , natural indirect effects, as defined as causal pathways through single mediators, are identified since these conditions imply that the given mediators are independent given exposure and baseline covariates VanderWeele and Vansteelandt 2013). Recently, Lange et al (2014) demonstrated how independent intermediate pathways can be assessed in a single natural effect model using the weightingbased approach.…”
Section: Intermediate Confounding: a Joint Mediation Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, if the aforementioned ignorability conditions A1-A4 hold with respect to each mediator separately 11 , natural indirect effects, as defined as causal pathways through single mediators, are identified since these conditions imply that the given mediators are independent given exposure and baseline covariates VanderWeele and Vansteelandt 2013). Recently, Lange et al (2014) demonstrated how independent intermediate pathways can be assessed in a single natural effect model using the weightingbased approach.…”
Section: Intermediate Confounding: a Joint Mediation Approachmentioning
confidence: 99%
“…Alternatively, the total causal effect can be decomposed into the effect transmitted through L and M simultaneously and the effect not mediated by any of the given mediators ( VanderWeele and Vansteelandt 2013;VanderWeele, Vansteelandt, and Robins 2014). Although such a joint mediation approach might not target the initial mediation hypothesis, it may still shed some light on the underlying causal mechanisms if there are reasons (either theoretical or empirical) to question the validity of condition A4 (with respect to a single mediator) 12 , since this decomposition relies on a weaker set of ignorability assumptions.…”
Section: Intermediate Confounding: a Joint Mediation Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…at the same time SCC and milk were collected) was unavailable and was replaced by information on CFU observed at three consecutive dates. If we had obtained information on test-day CFU, the mediation model would have included two 'causally ordered' mediators (CFU and SCC), with test-day CFU affecting test-day SCC (VanderWeele and Vansteelandt, 2014). With such model, it is possible to compute eight estimates of milk loss not mediated by any changes in SCC and CFU, eight estimates of milk loss mediated only by changes in CFU, eight estimates of milk loss mediated by changes in SCC alone and eight estimates of milk loss mediated by changes in both SCC and CFU (Albert and Nelson, 2011).…”
Section: Discussionmentioning
confidence: 99%